An Exploration of the Motivations and Career Development of Younger People Going on Volunteer Self-Initiated Expatriation - Hale, Cassidy (Auckland University of Technology, 2018)
Globalisation has fostered international mobility and subsequently, international careers. In New Zealand, international travel, or the ‘OE’ (overseas experience), has become a cultural norm and is a common phenomenon among younger people who want to explore the world. In the international mobility literature, the motivations and career development of corporate expatriates are widely discussed; however, in the self-initiated expatriation (SIE) literature, these issues are less understood with studies focusing primarily on professionals (Dickmann, Doherty, Mills & Brewster, 2008). The SIE literature suggests that international volunteerism is also a valid SIE experience (Andresen & Gustschin, 2013) and although SIE remains under theorised (Doherty, Richardson & Thorn, 2013), volunteer self-initiated expatriation (volunteer SIE) is an even more limited field of research. While there is an emergent literature on the motivations and career development of volunteer self-initiated expatriates (Fee & Gray, 2011; Hudson & Inkson, 2006), the experiences of younger volunteer self-initiated expatriates are not specifically addressed. This study explores the motivations and career development resulting from SIE undertaken by younger volunteers. As a qualitative study, a reflexive and interpretive methodology (narrative inquiry) was used to conduct and analyse seven in-depth interviews. A subjective epistemology, based on real world experiences, was fundamental to this research process and a three-phase analytical framework was developed, with findings presented in two sections: motivations and career development. This study found that while altruistic factors were important, individuals were mainly motivated to pursue volunteer SIE for personal reasons, including a desire for new and authentic travel experiences, which included a drive to meet new people. A further motivating factor was participants’ desire to escape as some felt confused as to which career path to pursue. Volunteer SIE provided the participants with space to further consider these crucial career decisions. Timing and context, such as having adequate funds and freedom from family commitments, were important enablers, freeing participants to engage in volunteer SIE. Despite seeking an escape from career decision-making, most participants did not pursue volunteer SIE for career enhancement, although this accrued unexpectedly. The main career outcomes discussed in this study related to the development of communication skills and networks, a new career outlook, and enhanced employability. In addition, personal development was also an important outcome and included a number of personal outcomes: an increase in motivation and confidence; greater resilience, adaptability and tolerance; gratitude; and greater self-awareness, factors which also support career enhancement. This study addresses a gap in the literature and contributes to the wider SIE, international volunteering, and careers literatures. Firstly, it is one of the few studies on younger volunteer self-initiated expatriates. Secondly, this study provides further evidence that the international volunteer experience fits within the SIE construct. Furthermore, this study reports that volunteer self-initiated expatriates are more inclined to go abroad to escape their careers, as compared to their SIE counterparts who predominantly go abroad for personal reasons. Finally, the study confirms previous research on SIE that personal development is a major outcome for volunteer self-initiated expatriates.
Keywords: SIE; Career development; Motivations; Volunteer SIE; Younger people; Self-initiated expatriation; Expatriation; Globalisation; International mobility